THE CONSEQUENCES OF ILLEGAL MINING IN THE ENVIRONMENT: PERSPECTIVES BEHAVIORAL, KNOWLEDGE AND ATTITUDE - Ali, Muhammad Ichsan (Three E Science Institute, 2019)
Environmental problems can overcome by changing the mental attitude of humans as environmental destroyers to humans who are aware of their environment. The focus in research is to find out and then interpret the results obtained related to the presence or absence of influence between the level of knowledge and attitudes of traditional miners on behavior. The number of samples used was 212 respondents spread over traditional mining areas of the community. Data is obtained from surveys using questionnaire instruments and interviews with traditional miners. The data is then analyzed Structural Equation Model (SEM) using IBM AMOS 23. The results of validation and reliability and goodness of fit (GOF) indicate that the model is feasible and fit. The results of the analysis show that there is a significant impact between the variables of knowledge and attitudes towards the behavior of the mining community. The condition of enough knowledge is not able to change people's behavior to manage the environment. The results obtained are the same as attitudinal variables that show contra to the environment. All ways are done to get profits without seeing the consequences. The attitude of the government must be more assertive in controlling illegal mining that has damaged the surrounding environment. Humans who are aware of their environment are humans who already understand and apply attitudes and behaviors that care about the environment and apply the principles of ecology and environmental ethics.